Effects of wolf removal on livestock depredation recurrence and wolf recovery in Montana, Idaho, and Wyoming. Issue 8 (23rd September 2015) - Bradley, Elizabeth H.; Robinson, Hugh S.; Bangs, Edward E.; Kunkel, Kyran; Jimenez, Michael D.; Gude, Justin A.; Grimm, Todd
ABSTRACT Wolf (Canis lupus) predation on livestock and management methods used to mitigate conflicts are highly controversial and scrutinized especially where wolf populations are recovering. Wolves are commonly removed from a local area in attempts to reduce further depredations, but the effectiveness of such management actions is poorly understood. We compared the effects of 3 management responses to livestock depredation by wolf packs in Montana, Idaho, and Wyoming: no removal, partial pack removal, and full pack removal. We examined the effectiveness of each management response in reducing further depredations using a conditional recurrent event model. From 1989 to 2008, we documented 967 depredations by 156 packs: 228 on sheep and 739 on cattle and other stock. Median time between recurrent depredations was 19 days following no removal (n = 593), 64 days following partial pack removal (n = 326), and 730 days following full pack removal (n = 48; recurring depredations were made by the next pack to occupy the territory). Compared to no removal, full pack removal reduced the occurrence of subsequent depredations by 79% (hazard ratio [HR] = 0.21, P < 0.001) over a span of 1, 850 days (5 years), whereas partial pack removal reduced the occurrence of subsequent depredations by 29% (HR = 0.71, P < 0.001) over the same period. Partial pack removal was most effective if conducted within the first 7 days following depredation, after which there was only a marginally significant difference between partial pack removal and no action (HR = 0.86, P = 0.07), and no difference after 14 days (HR = 0.99, P = 0.93). Within partial pack removal, we found no difference in depredation recurrence when a breeding female (HR = 0.64, P = 0.2) or ≥1‐year‐old male was removed (HR = 1.0, P = 0.99). The relative effect of all treatments was generally consistent across seasons (spring, summer grazing, and winter) and type of livestock. Ultimately, pack size was the best predictor of a recurrent depredation event; the probability of a depredation event recurring within 5 years increased by 7% for each animal left in the pack after the management response. However, the greater the number of wolves left in a pack, the higher the likelihood the pack met federal criteria to count as a breeding pair the following year toward population recovery goals. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.